After the "Great Recession": Excluding "Able-Bodied" Adults from Food Entitlements in the United States. Issue 4 (2nd October 2017) - D'Angelo, Karen; Libal, Kathryn; Seymour, Nicole; Hamel, Renee
ABSTRACT: A little-known provision to the Supplemental Nutrition Assistance Program (SNAP), excluding those who are "able-bodied adults without dependents" (ABAWDs) from accessing long-term benefits without conforming to work requirements or eligibility guidelines, was recently reinstated at federal and state levels. States have considerable discretion in implementing the ABAWD provision, resulting in differential access to SNAP benefits. This article provides an analysis of the historical and political context of the ABAWD provision and its relevance to social work. An examination of several states' different approaches to implementing the ABAWD rule underscores the limits of this policy and the consequent need for social work engagement and advocacy.